Pemetrexed-induced mucocutaneous hyperpigmentation in an atypical case of malignant pleural mesothelioma - Richa Tyagi; Anand Srivastava; Sanjeev Kumar Verma; Rajiv Garg; Preeti Agarwal (Indian Journal of Case Reports, 2021)
Development of cutaneous adverse effects secondary to pemetrexed is an uncommon occurrence. Here, we present an unusual case of a 22-year-old young male who developed malignant pleural mesothelioma without having any known risk factors. When started on first-line chemotherapy with pemetrexed and cisplatin, he developed hyperpigmented macular rashes over the palms, soles, and the dorsum of the tongue. Although, the better outcome has been reported previously in young patients in terms of response to chemotherapy, unfortunately, our patient had a rapid progression and poor outcome. Our case did not have a favorable course though and rapidly succumbed.